Encouragement of the Public as the Key to an Inclusive and Participatory Intervention - OEISM, Colectivo (Cuadernos de Trabajo Social, 2012)
In recent years, the debate on inequality has vigorously resurfaced: the lack of reduction in poverty rates, the increase in the gap between rich and poor, the distancing of the large power and decision-making structures, and the emergence of critical voices demanding the implementation of human rights in the context of a global society in crisis. Within this context and based on the notion of citizenship, which implies access and development of a set of rights and duties for the satisfaction of human needs and community life, this article describes the experience the «Observatory on Exclusion and Processes of Inclusion in the Community of Madrid» (OEISM) with groups in situations of exclusion aimed at the development of their community ties and full social participation.
Keywords: exclusion; citizenship; participation; human needs; social rights